L’espace romanesque dans les « Echelles du Levant » d’Amin Maalouf - Nabti, Amor (Journal of Human Sciences, 2016)
Room for research is great varied (fruitful) witch a novel offers for analysis. True it is an appropriate and efficient means for conveying the symbolic, poetic and referent of the subject in hand.